PAPUA "NOKEN" LOCAL WISDOM FOR THE STRENGHTNESS OF DEMOCRATIC PANCASILA VALUES IN INDONESIA - Kayame, Yohanes (JURNAL SETIA PANCASILA, 2023)
This paper discusses noken Papua as a local wisdom that gives its own meaning in democracy in Indonesia. For Papuans, noken has its own value for their lives. Because noken cannot be underestimated its existence in Papuan human civilization. There are many values ??of life that can be explored as principles in life. In this context, noken represents values ??for Pancasila democracy in Indonesia. For example, consensus, social, unity, justice, dignity as a human being and human personal relationship with God. The methodology in this paper uses literature study, by analyzing books, scientific journals and magazines. In addition, by developing the opinions of Papuan leaders who have talked about noken and Pancasila democracy. This writing contributes to developing democratic maturity in the life of the nation and state through the values ??obtained from Noken as a local Papuan wisdom. Thus noken is not only an inanimate object, but contains living values ??for democracy in Indonesia. So noken is the ancient heritage of the Papuan people who give life values.